Conduct problems among middle adolescents in the community settings: A concept analysis - Fauzan Saputra; Penpaktr Uthis; Sunisa Sukratul (Belitung Raya Foundation, Indonesia, 2023)
Background: Adolescent problem behavior in research and practice has been traditionally categorized as Oppositional Deviant Disorder and Conduct Disorder. However, a significant number of adolescents remain underdiagnosed. To address this issue, the term “Conduct Problem” has emerged as a commonly used descriptor for those who have not yet received a formal diagnosis, particularly within the community. It is crucial for nurses to comprehend the characteristics of these conduct problems to address them effectively. Objective: This concept analysis aimed to clarify the concept of conduct problems among adolescents aged 14 to 16, specifically within community settings. Methods: The concept analysis followed Walker and Avant’s approach. The usage of the concept was examined in five databases (PsyINFO, ProQuest, PubMed, ScienceDirect, Scopus), which yielded 41 relevant studies for comprehensive analysis. Results: The identified attributes of conduct problems in adolescents included oppositional problems, antisocial problems, and criminal-related problems. These conduct problems were found to have antecedents stemming from personal, parental, and environmental factors. Furthermore, the consequences of conduct problems significantly impacted both middle adolescents and their parents. Conclusion: The findings of this concept analysis contribute to a better comprehension of the concept of conduct problems among middle adolescents in community settings. The insights gained from this analysis will assist in using this term more effectively in research and nursing practice, ultimately leading to improved care and support for affected adolescents and their families.